Fiber-reinforced mortar composition and mortar thereof
Patent Information
- Application Number
- JP2021043106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-17
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-03-17
AI Technical Summary
【0010】 本発明によれば、繊維の分散性に優れ、且つ、施工性、速硬性及び長期強度の発現性に優れる繊維補強モルタル組成物及びそのモルタルを提供することができる。
Smart Images

Figure 0007638741000003 
Figure 0007638741000001 
Figure 0007638741000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber-reinforced mortar composition and a mortar thereof. [Background technology]
[0002] In recent years, the demand for ultra-high rise, large scale and high durability of architectural and civil engineering structures has become clearer. In order to realize such structures, high-strength mortars are being developed. As high-strength mortars, for example, ultra-high-strength mortars characterized by containing at least cement, pozzolanic fine powder, fine aggregate with a particle size of 3.5 mm or less, a water-reducing agent and water have been disclosed (Patent Document 1).
[0003] Concrete used in various structures is inherently highly durable, but parts of it may deteriorate depending on the structure and the environment in which it is used. If such deterioration occurs, the functionality of the structure may decrease, so repair and reinforcement of the deteriorated parts are necessary. For example, a fiber-reinforced mortar composition containing cement, fly ash, fine aggregate coated with a liquid shrinkage reducing agent, a superplasticizer, an expansive agent, a powdered polymer, a thickener, and short fibers is used to repair and reinforce the deteriorated parts (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-043234 A [Patent Document 2] JP 2011-121795 A Summary of the Invention [Problem to be solved by the invention]
[0005] When a structure using high-strength mortar deteriorates, materials to repair and reinforce the deteriorated area are also required to have high strength. However, high-strength mortar often has a low water-cement ratio, and when fibers are mixed into it, the kneadability and dispersibility of the fibers can become an issue.
[0006] In addition, when the time available for construction work is limited, such as in partial repair work of structures such as roads and railways, repair materials that are easy to mix and quickly develop strength after construction are required. However, as mentioned above, when fibers are mixed into high-strength mortar, the kneadability and dispersibility of the fibers can become problematic, making it difficult to balance the ease of preparation of the mortar with workability, rapid hardening, and the ability to develop long-term strength.
[0007] Therefore, an object of the present invention is to provide a fiber-reinforced mortar composition which is excellent in fiber dispersibility and is also excellent in workability, rapid hardening properties and long-term strength development, and a mortar made from the same. [Means for solving the problem]
[0008] As a result of intensive research into the above-mentioned problems, the present inventors have found that by adjusting the ignition loss of the binder and blending a specific amount of metal fibers having a specific shape, it is possible to obtain a fiber-reinforced mortar composition and a mortar therefor that have excellent fiber dispersibility and are excellent in workability, rapid hardening properties, and long-term strength expression.
[0009] That is, the present invention relates to the following [1] to [6]. [1] A fiber-reinforced mortar composition comprising a binder comprising cement, calcium aluminates, gypsum, and a pozzolanic substance, and metal fibers, the binder having an ignition loss of 0.7 to 6.4 mass%, the metal fibers being contained in an amount of 1 to 24 parts by mass per 100 parts by mass of the binder, and the metal fibers having a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers so as to form an angle with the substantially straight portion. [2] The fiber-reinforced mortar composition according to [1], wherein the length of the approximately straight portion accounts for 50 to 95% of the total length of the metal fiber, and the deformed portion is formed by bending each of both ends of the metal fiber so as to form an angle of 30 to 160 degrees with the approximately straight portion. [3] The fiber-reinforced mortar composition according to [1] or [2], wherein the content of the cement is 45 to 80 parts by mass per 100 parts by mass of the binder. [4] The fiber-reinforced mortar composition according to any one of [1] to [3], wherein the metal fibers have an aspect ratio of 25 to 150. [5] The fiber-reinforced mortar composition according to any one of [1] to [4], further comprising an expansive agent. [6] A fiber-reinforced mortar comprising the fiber-reinforced mortar composition according to any one of [1] to [5] and water, the content of the water being 20 to 45 parts by mass per 100 parts by mass of the binder. Effect of the Invention
[0010] According to the present invention, it is possible to provide a fiber-reinforced mortar composition having excellent fiber dispersibility, as well as excellent workability, rapid hardening properties and long-term strength development, and a mortar made from the same. [Brief description of the drawings]
[0011] [Figure 1] 1(a), (b), (c), (d), (e) and (f) are schematic diagrams illustrating the shapes of metal fibers to be blended in the fiber-reinforced mortar composition according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing is a schematic diagram, and the size of each component is not limited to those shown in the drawings.
[0013] The fiber-reinforced mortar composition of the present embodiment comprises a binder consisting of cement, calcium aluminates, gypsums, and a pozzolanic substance, and metal fibers, wherein the binder has an ignition loss of 0.7 to 6.4 mass%, the metal fiber content is 1 to 24 parts by mass per 100 parts by mass of the binder, and the metal fibers have a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers at an angle to the substantially straight portion.
[0014] The binder according to this embodiment is composed of four components: cement, calcium aluminates, gypsum, and a pozzolanic substance.
[0015] Various types of cement can be used, including, for example, various Portland cements such as normal, early strength, super early strength, low heat and moderate heat, ecocement, rapid hardening cement, etc. As the cement, normal Portland cement and early strength Portland cement are preferred from the viewpoint of easily achieving both rapid hardening and fluidity. One type of cement may be used alone, or two or more types may be used in combination.
[0016] The content of cement is preferably 45 to 80 parts by mass, more preferably 50 to 75 parts by mass, and even more preferably 55 to 70 parts by mass, relative to 100 parts by mass of the binder. If the content of cement is within the above range, the strength development is further improved.
[0017] Calcium aluminates are classified as C3A, C2A, C, where CaO is C, Al2O3 is A, Na2O is N, and Fe2O3 is F. 12 Calcium aluminate with a mineral composition indicated as A7, CA, or CA2, calcium aluminoferrite indicated as C4AF, calcium aluminate with halogen as a solid solution or as a substitute, C3A3·CaF2, etc. 11A general term for calcium haloaluminates including calcium fluoroaluminates designated as A7·CaF2, calcium sodium aluminates designated as C8NA3 or C3N2A5, calcium lithium aluminate, alumina cement, and calcium sulfoaluminates designated as C3A3·CaSO4. These calcium aluminates can be crystalline, amorphous, or a mixture of amorphous and crystalline. The calcium aluminates may be used alone or in combination of two or more. From the viewpoint of further improving early strength development, the fineness of calcium aluminates is set to 3000 cm2 in terms of Blaine specific surface area. 2 / g or more, and 2 / g or more. The fineness of calcium aluminates is preferably 8000 cm2 in terms of Blaine specific surface area. 2 It is preferable that the molecular weight is not more than 1 / g.
[0018] The content of calcium aluminates is preferably 10 to 35 parts by mass, more preferably 11 to 30 parts by mass, and even more preferably 12 to 25 parts by mass, relative to 100 parts by mass of the binder. If the content of calcium aluminates is within the above range, the rapid hardening property tends to be more excellent.
[0019] Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, etc. As the gypsum, anhydrous gypsum is preferable from the viewpoint of further improving the strength development. One type of gypsum may be used alone, or two or more types may be used in combination.
[0020] The content of the gypsum is preferably 6.5 to 23 parts by mass, more preferably 7 to 20 parts by mass, and even more preferably 7 to 18 parts by mass, relative to 100 parts by mass of the binder. If the content of the gypsum is within the above range, the long-term strength development is further improved. From the viewpoint of further improving the long-term strength development, the fineness of the gypsum is set to 4500 cm in terms of Blaine specific surface area. 2 / g or more, and2 / g or more. The fineness of the gypsum is preferably 15,000 cm in terms of Blaine specific surface area. 2 It is preferable that the molecular weight is not more than 1 / g.
[0021] Examples of the pozzolanic substance include various fly ashes described in JIS A 6201:2015, and silica fume, slag powder, and amorphous aluminosilicate described in JIS A 6207:2016. From the viewpoint of being more excellent in long-term strength development and workability, silica fume and amorphous aluminosilicate are preferable as the pozzolanic substance. One type of pozzolanic substance may be used alone, or two or more types may be used in combination.
[0022] The content of the pozzolanic substance is preferably 1 to 24 parts by mass, more preferably 2 to 20 parts by mass, even more preferably 3 to 18 parts by mass, and particularly preferably 4 to 15 parts by mass, relative to 100 parts by mass of the binder. If the content of the pozzolanic substance is within the above range, it is more likely that both initial and long-term strength development will be compatible. From the viewpoint of further improving long-term strength development, the fineness of the pozzolanic substance is set to 5 m in terms of BET specific surface area. 2 / g or more, and 2 The fineness of the pozzolanic substance is preferably 30 m / g or more in terms of BET specific surface area. 2 It is preferable that the molecular weight is not more than 1 / g.
[0023] The ignition loss of the binder is 0.7 to 6.4% by mass. If the ignition loss of the binder is outside the above range, the kneadability, workability, initial strength development, etc. of the metal fiber are reduced. From the viewpoint of easily achieving excellent kneadability and strength development, the ignition loss of the binder is preferably 0.9 to 5% by mass, and more preferably 1.0 to 4.5% by mass.
[0024] Ignition loss can be adjusted by adjusting each material that makes up the binder, adjusting the amount of organic matter in the binder by heating, adjusting the amount of water in the binder by drying or wetting, etc. Ignition loss can be calculated by weighing out 1g of binder sample into an empty crucible, placing it in an electric furnace adjusted to 700℃, and igniting for 15 minutes, and then calculating from the change in weight before and after ignition.
[0025] Fig. 1 is a schematic diagram showing the shape of a metal fiber 10 according to this embodiment. The metal fiber 10 is composed of a substantially straight portion 1 and a deformed portion 2 formed by bending at least one end of the metal fiber 10 at an angle A with the substantially straight portion 1. As shown in Fig. 1, the angle A is the angle between the substantially straight portion 1 and a line connecting the point where the bending of the metal fiber 10 begins (start point 3) and the end of the metal fiber 10 included in the deformed portion 2 (end point 4).
[0026] The length of the approximately straight portion 1 is preferably 50 to 95%, more preferably 60 to 94%, and even more preferably 70 to 93% of the total length of the metal fibers 10. When the length of the approximately straight portion 1 is within the above range, the kneadability and workability of the mortar are further improved.
[0027] The shape of the deformed portion 2 is not particularly limited. The deformed portion 2 may be linear as shown in FIG. 1(a) or curved as shown in FIG. 1(b). The deformed portion 2 may be further folded in the middle. For example, the deformed portion 2 may be further folded once in the middle as shown in FIG. 1(c), or may be further folded three times in the middle as shown in FIG. 1(d). Even if the deformed portion 2 has a bend in the middle, the start point 3 of the deformed portion 2 is a point where the deformed portion 2 is in contact with the approximately straight portion 1, and the end point 4 is an end of the metal fiber 10 included in the deformed portion 2. The angle of the bend in the middle of the deformed portion 2 is not particularly limited. The metal fiber 10 may have a plurality of deformed portions 2. For example, the metal fiber 10 may have deformed portions 2 at both ends as shown in FIG. 1(e), or may have two deformed portions 2 at one end of the metal fiber 10 as shown in FIG. 1(f). From the viewpoint of further reducing dripping of mortar and improving workability, it is preferable that the metal fiber 10 has a deformed portion 2 at each end of the metal fiber 10 and is further folded one or more times along the way of the deformed portion 2, and it is more preferable that the ends of the deformed portion 2 are folded once along the way in a direction away from each other so as to be parallel to the approximately straight portion 1 (Figure 1(e)).
[0028] The angle A is preferably 30 to 160 degrees, more preferably 50 to 160 degrees, even more preferably 70 to 160 degrees, even more preferably 90 to 150 degrees, and most preferably 120 to 150 degrees. When the angle A is within the above range, the workability of the mortar is further improved. When the metal fiber 10 has multiple deformed portions 2, the respective angles A may be the same or different.
[0029] The total length of the metal fibers 10 is preferably 15 to 50 mm, more preferably 20 to 45 mm, and even more preferably 25 to 40 mm. If the total length of the metal fibers 10 is within the above range, the kneadability and workability of the mortar are further improved.
[0030] The aspect ratio (total length / diameter) of the metal fibers 10 is preferably 25 to 150, more preferably 30 to 100, and further preferably 40 to 65. When the aspect ratio is within the above range, the kneadability and workability of the mortar are further improved, and sagging is less likely to occur.
[0031] The metal fibers 10 are not particularly limited as long as they are made of metal, and examples thereof include steel fibers, stainless steel fibers, amorphous metal fibers, and fibers whose surfaces have been subjected to chemical or physical treatment. From the viewpoint of achieving both the kneadability and hardening properties of the mortar, steel fibers are preferred as the metal fibers 10. The metal fibers 10 may be used alone or in combination of two or more types.
[0032] The content of the metal fibers 10 is 1 to 24 parts by mass relative to 100 parts by mass of the binder. If the content of the metal fibers 10 is outside the above range, the dispersibility and initial strength development of the metal fibers 10 will decrease. From the viewpoint of easily achieving both the dispersibility and strength development of the metal fibers 10, the content of the metal fibers 10 is more preferably 2 to 15 parts by mass, and even more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the binder.
[0033] The fiber-reinforced mortar composition of the present embodiment may contain, in addition to the above components, fine aggregate, an expansive material, a water reducing agent, a setting retarder, and the like.
[0034] The fine aggregate is not particularly limited, and examples thereof include river sand, silica sand, crushed sand, kansui stone, limestone sand, slag aggregate, lightweight aggregate, etc. These fine aggregates may be used alone or in combination of two or more kinds.
[0035] The content of the fine aggregate is preferably 100 to 400 parts by mass, more preferably 150 to 350 parts by mass, and even more preferably 200 to 300 parts by mass, relative to 100 parts by mass of the binder. When the content of the fine aggregate is within the above range, it is easy to achieve both sufficient compressive strength and splitting tensile strength.
[0036] By including an expansive agent in the fiber-reinforced mortar composition, the compressive strength and dimensional change rate of the mortar become excellent. The expansive agent may be any JIS-compliant expansive agent (JIS A 6202:2008) that is generally used as an expansive agent for concrete. Examples of the expansive agent include an expansive agent mainly composed of free quicklime (quicklime-based expansive agent), an expansive agent mainly composed of auin (ettringite-based expansive agent), and a composite expansive agent of free quicklime and ettringite-forming material. The expansive agent may be used alone or in combination of two or more kinds. The expansive agent may have a Blaine specific surface area of 2000 to 6000 cm. 2 It is preferable to use one having a molecular weight of 1 / g.
[0037] The content of the expansive material is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, and even more preferably 1 to 3 parts by mass, relative to 100 parts by mass of the binder. If the content of the expansive material is within the above range, the compressive strength, dimensional change rate, etc. will be further improved.
[0038] The water reducing agent includes a high-performance water reducing agent, a high-performance AE water reducing agent, an AE water reducing agent, and a superplasticizer. Examples of such water reducing agents include those specified in JIS A 6204:2011 "Chemical admixtures for concrete". Examples of water reducing agents include polycarboxylic acid water reducing agents, naphthalene sulfonic acid water reducing agents, lignin sulfonic acid water reducing agents, and melamine water reducing agents. Among these water reducing agents, polycarboxylic acid water reducing agents are preferred from the viewpoint that the fluidity retention time can be easily ensured even with a small amount of addition. The water reducing agents may be used alone or in combination of two or more types.
[0039] The content of the water reducing agent is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, and even more preferably 0.3 to 1 part by mass, relative to 100 parts by mass of the binder. If the content of the water reducing agent is within the above range, the pot life is easily ensured and the fluidity is further improved.
[0040] By including a retarder in the fiber-reinforced mortar composition, it is easy to ensure a sufficient pot life even when the mixing temperature of the polymer cement mortar is high in summer. Examples of the retarder include organic acids or salts thereof such as citric acid, gluconic acid, malic acid, and tartaric acid; boric acid, borates such as sodium borate, phosphates, alkali metal carbonates, and alkali metal bicarbonates; and sugars. Among these, citric acid, citrates, tartaric acid, tartrates, and alkali metal carbonates are preferred. The retarder may be in the form of a powder or a liquid (for example, an aqueous solution, an emulsion, or a suspension). The retarder may be used alone or in combination of two or more.
[0041] The content of the setting retarder is preferably 0.1 to 7.5 parts by mass, more preferably 0.3 to 5 parts by mass, and most preferably 0.5 to 3.5 parts by mass, relative to 100 parts by mass of the binder. If the content of the setting retarder is within the above range, the pot life is further ensured and the initial strength development is less likely to decrease.
[0042] The fiber-reinforced mortar composition of the present embodiment may contain various admixtures within the range in which the effects of the present invention are not impaired. Examples of the admixtures include foaming agents, defoamers, thickeners, polymers for cement, waterproofing materials, rust inhibitors, shrinkage reducing agents, water retention agents, pigments, fibers, water repellents, efflorescence inhibitors, quick-setting agents (materials), quick-hardening agents (materials), stone powder, volcanic ash, air entraining agents, and surface hardeners.
[0043] The method for producing the fiber-reinforced mortar composition of the present embodiment is not particularly limited, and the composition can be produced, for example, by mixing the above components using a mixer such as a gravity mixer such as a V-type mixer or a tilting concrete mixer, a Henschel mixer, a jet mixer, a ribbon mixer, or a paddle mixer.
[0044] The fiber-reinforced mortar composition of the present embodiment can be prepared as a fiber-reinforced mortar by mixing with water, and the water content may be appropriately adjusted depending on the application. The water content is preferably 20 to 45 parts by mass, more preferably 22 to 40 parts by mass, and even more preferably 25 to 35 parts by mass, relative to 100 parts by mass of the binder. If the water content is within the above range, the kneadability of the metal fiber and the initial and long-term strength development are further improved.
[0045] The fiber-reinforced mortar of the present embodiment can be prepared using a kneading tool similar to that used for ordinary mortar compositions, and is not particularly limited. Examples of the kneading tool include a mortar mixer, a hand mixer, a tilting mixer, a biaxial mixer, and a pan mixer.
[0046] The fiber-reinforced mortar composition and fiber-reinforced mortar of the present embodiment are high-strength mortars, but also have excellent dispersibility of metal fibers. Therefore, they can be suitably used for repair and reinforcement of various structures and sites that require high strength. The construction method is not particularly limited, and can be selected from a method of making a formwork and filling it, a method of applying it with a trowel, a method of spreading it evenly using a vibrator, and the like. EXAMPLES
[0047] The present invention will be described below based on examples, but the present invention is not limited to these.
[0048] [material] Cement (C): High-early-strength Portland cement Calcium aluminates (CA): CaO / Al2O3=1.4, Vitrification rate: 40%, Blaine specific surface area: 5000cm 2 / g ·Gypsum (CS): Anhydrite, Brain specific surface area: 7000cm 2 / g Pozzolanic material (SF): Silica fume, BET specific surface area: 15m 2 / g Metal fiber 1: Steel fiber, total length: 30 mm, aspect ratio: 45, shape: shape shown in Figure 1(e), proportion of approximately straight parts to total length: 77%, each angle A: 150 degrees Metal fiber 2: Steel fiber, total length: 30mm, aspect ratio: 45, shape: linear Fine aggregate: Silica sand (grain size adjusted) Expansion material: lime-based expansion material, Blaine specific surface area: 3200 cm 2 / g Water reducing agent: Polycarboxylic acid-based high-performance water reducing agent · Retarder: Citric acid
[0049] [Mix design of fiber-reinforced mortar composition] The binders consisting of cement, calcium aluminates, gypsum and pozzolanic substances were used in the proportions shown in Table 1, and the mix was designed so that per 100 parts by mass of binder, the contents and types of metal fibers, 270 parts by mass of fine aggregate, 1.5 parts by mass of expansive material, 0.5 parts by mass of water reducing agent and 0.6 parts by mass of setting retarder were added in the amounts and types shown in Table 1. The fiber-reinforced mortar composition No. 6 is used as a reference example.
[0050] [Ignition loss of binder] The prepared binder was dried or wetted to adjust the loss on ignition. The loss on ignition was measured by weighing 1 g of binder sample into an empty crucible, placing it in an electric furnace adjusted to 700°C, and igniting it for 15 minutes, and calculating the loss on ignition from the change in weight before and after ignition.
[0051] [Table 1]
[0052] [Preparation of fiber-reinforced mortar] In an environment of 20°C, water was added to each of the fiber-reinforced mortar compositions so that the ratio was 30 parts by mass per 100 parts by mass of binder, and the mixture was mixed in a forced mixer for 120 seconds to produce approximately 25 L of mortar.
[0053] [Evaluation method] Each item was evaluated by the following methods. The evaluation results are shown in Table 2. 1) Fresh properties a) Dispersibility When preparing fiber-reinforced mortar using a forced mixing mixer, if the metal fibers were not uniformly dispersed due to the formation of clumps of metal fibers, etc., it was rated as poor (×), and if it was confirmed that the metal fibers were uniformly dispersed, it was rated as good (○). b) Sagging characteristics A concrete slab (300 x 300 x 60 mm) was placed on a 5% gradient, and fiber-reinforced mortar was applied to a thickness of 20 mm. The sagging was then smoothed out with a trowel and visually observed. Sagging was evaluated as poor (×), and no sagging was evaluated as good (○). 2) Compressive strength The compressive strength was measured at 3 hours and 28 days according to the Japan Society of Civil Engineers standard JSCE-G 5050-2010 "Method of compressive strength test for mortar or cement paste using cylindrical specimens (draft)". The dimensions of the specimen were 50mm in diameter and 100mm in height. The 28-day-old specimens were demolded the next day and cured in water until the specimens reached their maturity. Curing was always performed in a thermostatic chamber at 20℃.
[0054] [Table 2] [Explanation of symbols]
[0055] 10 metal fiber, 1 approximately straight section, 2 deformation section, 3 starting point, 4 end point, A angle
Claims
1. The present invention relates to a cement-based concrete structure, and more particularly to a concrete structure comprising a binder including cement, calcium aluminates, gypsums, and pozzolanic materials, and metal fibers; The ignition loss of the binder is 0.7 to 6.4% by mass, The content of the cement is 55 to 80 parts by mass relative to 100 parts by mass of the binder, The content of the calcium aluminates is 10 to 18 parts by mass relative to 100 parts by mass of the binder, The content of the gypsum is 6.5 to 23 parts by mass relative to 100 parts by mass of the binder, The content of the pozzolanic substance is 1 to 24 parts by mass per 100 parts by mass of the binder, The content of the metal fibers is 1 to 24 parts by mass relative to 100 parts by mass of the binder, A fiber-reinforced mortar composition, wherein the metal fibers have a substantially straight portion and a deformed portion formed by bending at least one end of the metal fibers at an angle of 30 to 160 degrees from the substantially straight portion, the total length of the metal fibers is 25 to 40 mm, and the aspect ratio of the metal fibers is 40 to 65.
2. 2. The fiber-reinforced mortar composition according to claim 1, wherein the length of the approximately straight portion accounts for 50 to 95% of the total length of the metal fiber, and the deformed portion is formed by bending each of both ends of the metal fiber so as to have an angle of 30 to 160 degrees with the approximately straight portion.
3. The fiber reinforced mortar composition according to claim 1 or 2, further comprising an expansive material.
4. The fiber-reinforced mortar composition according to any one of claims 1 to 3 and water, The fiber-reinforced mortar has a water content of 20 to 45 parts by mass per 100 parts by mass of the binder.
Citation Information
Patent Citations
Steel fiber for reinforcing concrete
JP1993262544A
Cement based self-leveling material
JP1995187745A
Rotary connector
JP1995320835A
High-flowable cement composition
JP1996183636A
Ultrahigh strength mortar
JP2004043234A